KUALITAS SISTEM INFORMASI MANAJEMEN DAN EFEKTIVITAS PENGAMBILAN KEPUTUSAN PADA PERUSAHAAN KONSTRUKSI DI JAWA BARAT DARI PERSPEKTIF: TEKNOLOGI INFORMASI, MANAJEMEN PENGETAHUAN DAN PENGENDALIAN INTERNAL - Fitri Anggaraeni, Annisa; Anisarida, An An; Janizar, Syapril; Amijaya, Dodi Tisna (Departement of Civil Engineering, Universitas Winaya Mukti, 2024)
Construction companies in carrying out their activities require management information systems and technology in decision-making. The purpose of this research is to know and analyze the impact of information technology, knowledge management, and internal control on the quality of management information systems, which implies the effectiveness of decision-making for construction companies in West Java, both simultaneously and partially. This study employs a quantitative, cross-sectional research method. The research population is 1160 construction companies in West Java, with a sample of 150 construction companies in West Java consisting of 3 observation units, namely project managers, site engineers, and site managers. The research findings reveal that information technology not only supports but also significantly enhances the quality of management information systems. Furthermore, knowledge management directly influences the improvement of a good quality management information system, which means that knowledge management has a direct and significant positive impact on the quality management information system. Information technology, knowledge management, and internal control can enhance effective decision-making through quality management information systems.